The 25th anniversary of the Journal of Civil Engineering and Management: editor’s introduction - Zavadskas, Edmundas Kazimieras; Antuchevičienė, Jurgita (Journal of Civil Engineering and Management, 2019)
In 2019, the Journal of Civil Engineering and Management commemorates its 25th year of publishing. Therefore, in this short introduction, the Editors would like shortly to overview Journal’s development and its current achievements. In addition, taking the opportunity, the Editors would like to thank the numerous Authors, the distinguished Advisory Editors and Editorial Board members, and the Reviewers who have contributed to the quality and the success of the Journal.